Digital Predistortion of Frequency-Multipliers-Based Wideband Millimeter-Wave Sources - Jaffri, Ifrah (University of Waterloo, 2020)
Radio frequency (RF) technology has seen unprecedented advancements over the past few decades. These advancements have been driven by continuously growing demand for wireless networks with higher capacity and radar and sensing technologies with higher accuracy and capabilities. These demands have been partially addressed using radio communication solutions with operating frequencies predominantly in the giga-hertz (GHz) bands. However, the extensive penetration of radio communication into various industry sectors has spurred a shift to the millimeter-wave (mm-wave) bands, where abundant spectrum resources are available. Yet, this shift brings with it several challenges, especially to the design of RF transceivers. Some of these challenges are due to the increased parasitics and reduced performance (efficiency, output power, gain) of most of the semiconductor technologies as the operating frequency increases. Others are associated with the propagation at mm-wave which is characterised with significant losses. The limited maximum oscillation frequency of underlying transistors in power amplifier (PA) is one main reason for reduced performance of high frequency signal source. In this work, a frequency multiplier-based high frequency and high quality signal transmitter (TX) architecture is proposed which outperforms PA-based TXs. Nevertheless, some linearization techniques, for example digital predistortion (DPD), have to be deployed to mitigate the distortions caused by frequency multipliers in the TX chain. This work proposes a novel DPD scheme for mitigating the effects of nonlinear distortion caused by frequency multipliers when driven with wideband vector modulated signals. An effective pruning strategy is applied to limit the number of coefficients and consequently limit the complexity of the DPD scheme while maintaining excellent linearization capacity. Extensive tests are conducted using different mm-wave frequency multipliers for proof of concept validation. These multipliers include two frequency doublers (25 GHz, 28 GHz), a tripler (63 GHz), and a quadrupler (25 GHz), and are driven by vector modulated signals with an instantaneous bandwidth (BW) of up to 400 MHz. With 44 coefficients or less, the proposed DPD allowed for excellent cancellation of the distortions exhibited by the frequency doublers and improved the error vector magnitude (EVM) and adjacent channel power ratio (ACPR) from about 21% and 21 dB to 1.8-0.8% and 47-54 dB for the different test signals. Similarly, in the case of the frequency tripler, the EVM and ACPR improved from 8% and 30 dB to less than 1.7% and 45-51 dB after applying the proposed DPD scheme with 57 coefficients for the different test signals used. Finally, in the case of the frequency quadrupler, which is composed of a cascade of two frequency doublers, the proposed DPD scheme was able to achieve similar quality of output signal with higher number of coefficients. Moreover, the high frequency signals experience significant attenuation due to non-negligible parasitic effects in the circuit and considerable free-space path loss over-the-air (OTA). As a result, even a frequency multiplier-based TX architecture shows limited output power. However, various large-scale multiple antenna (LSMA) architectures have been studied in the literature to improve the radiation output power and beam-steering capability of the TX. In this work, a frequency-multiplier-based radio frequency (RF) beamforming architecture suitable for the generation/transmission of high-frequency vector-modulated signals is proposed. Additionally, in order to tackle the non-linearity of the frequency multipliers, the proposed architecture incorporates a single-input-single-output DPD function that has been carefully synthesized to guarantee excellent EVM and ACPR for the signals received in the far-field. A 2×2 beamforming array was built using off-the-shelf frequency doublers and printed circuit board based patch antennas, all operating at 28 GHz, to serve as the device-under-test in the validation experiments. OTA experiments confirmed the ability of the proposed architecture to successfully generate orthogonal frequency division multiplexing (OFDM) signals. For instance, EVMs as low as 0.9% and 2.5% and ACPRs equal to 52 dB and 47 dB, were obtained for modulation BWs equal to 100 MHz and 400 MHz, respectively.
Keywords: millimeter waves, transmitters, digital predistortion, frequency multiplier, radio-frequency beamforming